The Impact of Perfect Competition Market Structure on Firm Performance in the Coffee Culinary Industry - Johnny Chandra; Farah Fitria Ramadhani; Rahmat Dinul Paqi; Muh. Rafli Ramadhan (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
This study examines the influence of perfect competition market structure on firm performance within the coffee culinary industry. A qualitative approach was employed, utilizing data collection methods such as surveys, interviews, observations, and documentation involving key stakeholders in the culinary business. The findings reveal that the coffee industry in Makassar, specifically exemplified by Kopi Break, operates within a perfect competition market structure. In the short run, market equilibrium is demonstrated by the balance between supply and demand at Kopi Break. The study highlights that one effective method for analyzing short-term market equilibrium involves assessing the impact of shifts in the supply curve on market balance. Additionally, it was found that the market structure in the culinary industry is heavily influenced by the behavior and strategic decisions of firms. This research provides valuable insights into how perfect competition conditions affect business performance and decision-making within the coffee culinary industry, emphasizing the importance of firm behavior in maintaining market equilibrium.